PERSONAL AND PROFESSIONAL DEVELOPMENT OF FUTURE EDUCATORS IN THE PROCESS OF EDUCATIONAL PRACTICES - Ivaniuk, Hanna; Venhlovska, Olena; Antypin, Yevhen (Continuing Professional Education: Theory and Practice, 2020)
The article highlights the features of content and technology support of personal and professional development of future teachers in the process of educational practices. Abovementioned ideas are presented here in an anthropological dimension. Personal and professional development of students is shown as a process aimed at modelling the personal and professional qualities of future teachers, ability and willingness for development and self-development. Specifics that have been named are for producing new ideas and practices based on acquired knowledges for creation own trajectory of professional development. The value-personal, search and research, reflective components and the 21st century skills are defined as important components of personal and professional development of students. The exploration describes empirical results of research on the formation of abovementioned components in students of specialties «Preschool education» and «Primary education» before their practices. It has been found that future teachers strive for personal and professional development however they don’t have enough skills to plan their actions of self-development. According to the empirical results of this study the scientific and pedagogical staff of Department of Pedagogy and Psychology of Pedagogical institute of Borys Grinchenko Kyiv University developed programs and recommendations for the organization of educational practices. The article describes the content, forms, methods of development of components of personal and professional development of students in the course of educational practices conducted in the preschool and primary school institutions in Kyiv. The essence of such interactive forms as: a roadmap, reflection, a blog, an individual portfolio of personal and professional growth is revealed. The proposed forms of work contribute to the students’ willingness to evaluate the results of their professional activity, to form the ability to work as a team and alone, to be openminded to the opinions of others in educational space, to find new ways of solving pedagogical goals, etc. The empirical results of the study show the positive dynamics of students’ development in value-personal, search and research, reflective components and 21st century skills in the course of proposed forms of work. This testifies to the effectiveness of the created content and technology support for the development of components of personal and professional development of students in the process of educational practices.